Humberto Mauro, Cinema, História - César Júnior, Sérgio (Imagofagia, 2021)
Sobre Morettin, Eduardo Victorio. Humberto Mauro, Cinema, História. São Paulo: Alameda, 2013, 496 pp., ISBN: 9788579391408 Resumen: reseña sobre el libro de Morettin, Eduardo Victorio. Humberto Mauro, Cinema, História. São Paulo: Alameda, 2013, 496 pp., ISBN: 9788579391408 Palabras clave: reseña, Morettin, Eduardo Victorio, Humberto Mauro, Cinema, História